Biocomputational Architecture Based on Particle Physics - Heidari, Farahbod; Mahdavinejad, Mohammadjavad; Werner, Liss C.; Roohabadi, Maryam; Sarmadi, Hanieh (Frontiers in Energy Research, 2021)
Domestic Greywater generated by household chores has a Major Contribution to environmental pollution and is also the best-untapped energy source. Since the past decade, in the Different fields, enormous efforts were made to reach the Bio-Energy from Bio-Waste. These efforts consist of a wide range of Thermochemical, Bio-Chemical, and Microbial Fuels, etc. However, all these efforts are in their infancy. They have high cost and be Efficient on a Large-Scale; furthermore, these efforts used a non-intelligent process that has led to a lack of development in this type of Review. This Ongoing Research presents the smart design process that comes to Hybrid Energy via the intersection of Computation, Wastewater, and Microorganisms that aims to introduce the novel Bio-Computational Machine based on particle physics. Therefore, we investigate the Mixture of the Microbial fuel cells, specifically "Spirulina" Micro-Algae, and household chores Greywater. In the computational framework, we propose High-Precise fluid simulation with the advantage of particle's position and dynamic physics for Conversion of the Mixture of "Spirulina Medium" and household chores Greywater enables Output Energy control, Flow, and management of the type of solution mix, by transferring this data from the modules to the Computational Environment. Finally, these dataset's behavior simulates based on the physical properties of each particle. The procedure works in a parametric computer-aided design (CAD) environment and through Grasshopper within Rhinoceros Software by syncing Bio-Computational Machine to the Computational Environment. The Solenoid Valve and fluid flow controller between the nutritious tank and Energy Conversion Tank measure nutritional consumption and sends it to the Digital Environment numerically with an Arduino-Uno board kit. These batch numerical signals are stored in our local database then combined with the particle physics engine and simulate the materials' behavior, also provide the ability to control digitally.